RECURRENT RESPIRATORY DISEASES IN CHILDREN AND THE STATE OF HUMORAL IMMUNITY - A. A. Lebedenko; A. M. Levchin; E. V. Nosova (Медицинский вестник Юга России, 2015)
Purpose: the aim of the study was to explore the features of humoral immunity in children 2-4 years with recurrent respiratory diseases attending organized children’s groups.Materials and Methods: 158 children aged 2 to 4 years were examined. 126 patients suffered from recurrent respiratory diseases (basic group) and 32 healthy children (control group).Results: the lowest serum levels of IgA and IgM were marked in children with recurrent respiratory diseases comparison with a group of healthy children (p<0.01). We have found in the study of factors of humoral immunity a positive correlation the levels of IgA with IgG (r=0,29, p<0,001) and IgE with IRI (r=0,24, p<0,01). An inverse correlation was also found between IgM to IgG (r=-0,37, p<0,001), and IgM to IgE (r=-0,16, p<0,05). Thus, correlative interrelations were determined in the patients of basic group, represented the disbalance of the immune system in children with RRD.Summary: these changes were formed as a result of prolonged stimulation of the immune system and infectious agents and led to tensions of the processes of immune response and depletion of reserve capacity in children.